Indoor carrier phase positioning algorithm based on time-varying clock error elimination - Shaoshuai FAN; Zhiqiang RONG; Hui TIAN; Lihua LI; Xiaoqi QIN (Tongxin xuebao)
To solve the problems of low positioning accuracy of traditional positioning algorithm and unsynchronized system clock in indoor wireless environment, a 3D positioning algorithm was proposed based on the fusion of triple-differential carrier phase measurements and time difference of arrival (TDoA) positioning.Considering that the time-varying clock offsets between wireless access points lead to lower positioning accuracy, the measurements from a reference terminal were used to eliminate the influence of time-varying clock offsets.The relative positions were estimated based on triple-differential carrier phase measurements, which were fused with unbiased differential TDoA positioning results to obtain the interim estimated positions.Furthermore, the carrier phase observation equations were linearized by Taylor expansion method, and the high-accuracy positioning was realized by solving the integer ambiguities.Simulation results show that the proposed algorithm eliminates the influence of time-varying clock offsets on positioning performance, and the integer ambiguities are resolved in a short time to achieve high-accuracy positioning.